Magnetic porous biochar with high specific surface area derived from microwave-assisted hydrothermal and pyrolysis treatments of water hyacinth for Cr(Ⅵ) and tetracycline adsorption from water. (November 2021) - Qu, Jianhua; Wang, Siqi; Jin, Laiyu; Liu, Yang; Yin, Renli; Jiang, Zhao; Tao, Yue; Huang, Junjian; Zhang, Ying
Graphical abstract: Highlights: Two-step microwave-assisted processes were used to prepare magnetic porous biochar. The MPBCMW3 possessed high SBET of 2097.51 m 2 /g with superior adsorption performance. The maximum uptake of Cr(VI) and TC by MPBCMW3 were 202.61 mg/g and 202.62 mg/g. Chemical interactions (e.g. complexation and reduction) enhanced the Cr(VI) binding. Pore filling, hydrogen bonding and π-π stacking interactions promoted the TC uptake. Abstract: Magnetic porous water hyacinth-derived biochar (MPBCMW3 ) was synthesized via two-step Microwave (MW)-assisted processes. Characterization results not only testified high specific surface area (2097.50 m 2 /g) of the MPBCMW3 assisted by MW-assisted pyrolysis, but also revealed its favorable magnetism derived from MW-assisted hydrothermal process. The MPBCMW3 possessed pH-dependent monolayer adsorption capacities of 202.61 and 202.62 mg/g for Cr(VI) and TC with quick attainments of uptake equilibrium within 150 and 200 min. Moreover, the Cr(VI) and TC uptake were substantially steady under the interference from multifarious co-existing ions with slight decline after three adsorption–desorption cycles. Furthermore, the MPBCMW3 was demonstrated to achieve excellent Cr(VI) binding primarily through complexation, electrostatic interaction, reduction and ion exchange, while presenting outstanding TC removal via pore filling, π-π stacking, hydrogen bonding force, electrostatic interaction and complexation. All these findings suggested the MPBCMW3 synthesized by MW-assisted processes as an excellent adsorbent for purification of Cr(VI) and TC-contaminated water.